Transcriptome-wide analysis reveals insight into tumor suppressor functions of 1B3, a novel synthetic miR-193a-3p mimic - Marion T.J. van den Bosch; Sanaz Yahyanejad; Mir Farshid Alemdehy; Bryony J. Telford; Thijs de Gunst; Harm C. den Boer; Rogier M. Vos; Marieke Stegink; Laurens A.H. van Pinxteren; Roel Q.J. Schaapveld; Michel Janicot (Elsevier, 2021)
Emerging data show that microRNA 193a-3p (miR-193a-3p) has a suppressive role in many cancers and is often downregulated in tumors, as compared to surrounding normal tissues. Therefore, mimics of miR-193a-3p could be used as an attractive therapeutic approach in oncology. To better understand and document the molecular mechanism of action of 1B3, a novel synthetic miRNA-193a-3p mimic, RNA sequencing was performed after transfection of 1B3 in six different human tumor cell lines. Genes differentially expressed (DE) in at least three cell lines were mapped by Ingenuity Pathway Analysis (IPA), and interestingly, these results strongly indicated upregulation of the tumor-suppressive phosphatase and tensin homolog (PTEN) pathway, as well as downregulation of many oncogenic growth factor signaling pathways. Importantly, although unsurprisingly, IPA identified miR-193a-3p as a strong upstream regulator of DE genes in an unbiased manner. Furthermore, biological function analysis pointed to an extensive link of 1B3 with cancer, via expected effects on tumor cell survival, proliferation, migration, and cell death. Our data strongly suggest that miR-193a-3p/1B3 is a potent tumor suppressor agent that targets various key oncogenic pathways across cancer types. Therefore, the introduction of 1B3 into tumor cells may represent a promising strategy for cancer treatment.